1995
DOI: 10.1016/0014-5793(95)00058-h
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of smooth muscle caldesmon with calmodulin mutants

Abstract: The interaction of avian smooth muscle caldesmon with calmodulin (CAM) was investigated by studying the ability of selected mutant calmodulins to induce fluorescence changes in caldesmon. Different types of CaM mutants were used including point charge mutants, cluster mutations, and mutations which alter the calcium binding of CaM. The caldesmon binding properties were only slightly affected by E84K-CaM or by the double mutation E84Q/E120Q-CaM. Affinity of calmodulin to caldesmon was decreased 2-4 times by poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…Caldesmon-binding sites of calmodulin are not so well determined. It is supposed that calmodulin interacts with caldesmon in an extended conformation [9] and that both N-and C-terminal globular domains as well as the central α-helix of calmodulin are involved in caldesmon binding [10]. The data obtained on proteolytic fragments of calmodulin [11] and calmodulin mutants [12] agree with this suggestion and indicate that multiple sites of calmodulin interact with caldesmon.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…Caldesmon-binding sites of calmodulin are not so well determined. It is supposed that calmodulin interacts with caldesmon in an extended conformation [9] and that both N-and C-terminal globular domains as well as the central α-helix of calmodulin are involved in caldesmon binding [10]. The data obtained on proteolytic fragments of calmodulin [11] and calmodulin mutants [12] agree with this suggestion and indicate that multiple sites of calmodulin interact with caldesmon.…”
Section: Introductionmentioning
confidence: 57%
“…Knowing the total concentration of calmodulin and the stoichiometries of the complexes formed, we determined the total concentration of caldesmonbinding sites. This value was used to estimate apparent dissociation constants of caldesmon fragments from intact calmodulin by using a non-linear binding equation [10,11]. A similar approach was used when tryptic peptides of calmodulin were titrated with caldesmon fragments.…”
Section: Protein-protein Interactionmentioning
confidence: 99%
“…Different positioning of methionine side chains in the mutant may be the cause of this result, as three methionines, 71, 72 and 76, are close to the disulphide bond of C41\75. Medvedeva et al [35] also observed altered calmodulininduced changes in the fluorescence spectra of caldesmon for two N-terminal calmodulin mutants with alteration of the first or of the second Ca# + -binding loop of calmodulin.…”
Section: Discussionmentioning
confidence: 87%
“…Similarly we have observed that the C-terminal fragments, H2 and H7 with Trp-716 and -749 (659 and 692 in the chicken sequence) and 658C and H9 with Trp-749 and -779 (692 and 722), show a fluorescence intensity increase of the spectrum maximum of 33 % to 49 % and a shift of the maximum of 8 nm to 18 nm on interaction with calmodulin. Previous fluorescence intensity measurements for the interaction of caldesmon with calmodulin were performed at a fixed wavelength (320 nm) [7,9,14,35]. However, the intensities measured at 320 nm are the function of the fluorescence intensity change and the blue shift.…”
Section: Interaction Of Caldesmon-calmodulin Observed By Spectroscopimentioning
confidence: 99%
“…Several studies have been carried out on various mutant variants of the CaM central helix, including mutation or deletion of the acidic residues (Craig et al, 1987;Persechini et al, 1989Persechini et al, , 1991Gulati et al, 1990;VanBerkum et al, 1990;Raghunathan et al, 1993;Medvedeva et al, 1995Medvedeva et al, , 1999Tabernero et al, 1997). In general, the outcome has been CaM that has been functional but with a lower affinity towards target proteins.…”
Section: Discussionmentioning
confidence: 99%